MICRO RNA 182-3-P, 519-D-5P, 378-3P AS NON-INVASIVE PREDICTORS OF PREECLAMPSIA - Ali, Zaima; Zafar, Uzma; Tauseef, Ambreen; Zaki, Saima; Khaliq, Saba (Journal of Ayub Medical College Abbottabad, 2023)
Background: MicroRNAs (miRNAs) are an emerging field of interest in many diseases. Some of the miRNAs have been reported to be expressed differentially in diseased states of pregnancy. The current study was designed to measure and compare the levels of microRNA 182-3-p, 519-d-5p, and 378-3p and it was hypothesized that the microRNA 182-3-p, 519-d-5p, and 378-3p can be used as a non-invasive predictor of preeclampsia. Methods: Expression level of the miRNAs 182-3-p, 519-d-5p, and 378-3p was measured in the serum of preeclamptic and normal pregnancies by real-time PCR. Data was entered and analysed by Statistical Package for the Social Sciences 22 (SPSS). Results: Significantly high expression levels of MiRNA 182-3p, 519-d-5p and low levels of miR-378-3p were associated with preeclampsia (PE). Conclusion: The results revealed that miR-182-3p is a powerful predictor of PE with an Odds Ratio of 5.9 and can be used as a noninvasive, reliable predictor of PE to screen these patients at an early stage. Screening at early gestation with follow-up studies can emphasize the results